2016
DOI: 10.1186/s12906-016-1353-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory actions of selected natural substances on formation of advanced glycation endproducts and advanced oxidation protein products

Abstract: BackgroundAdvanced glycation endproducts (AGE) and advanced oxidation protein products (AOPP) arise as a result of excessive glycation and oxidation processes of proteins in hyperglycemia and oxidative stress conditions respectively, both in vivo and in vitro. In vivo these processes are especially intensified in patients with diabetes, and the adverse effects of AGE and AOPP are particularly unfavorable for the pathogenesis and aggravate the biochemical disturbances and clinical complications of diabetes. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…This was likely due to an increase in the total thiol groups, which decreases oxidative stress and protects the tissues [ 38 , 67 ]. Other studies have also reported similar results [ 65 , 66 ]. We observed that stress increases the lipoperoxidation values, which showed a time-dependent response to SMF exposure.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This was likely due to an increase in the total thiol groups, which decreases oxidative stress and protects the tissues [ 38 , 67 ]. Other studies have also reported similar results [ 65 , 66 ]. We observed that stress increases the lipoperoxidation values, which showed a time-dependent response to SMF exposure.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, AOPPs are proteins (albumin), and their aggregates are often damaged by oxidative stress [ 38 ]. They mostly comprise dityrosines, which allow crosslinking with disulfides through chlorinated oxidants, hypochloric acid, and chloramines, resulting in myeloperoxidase activity [ 65 , 66 ] and the formation of carbonyl groups [ 67 ]. These cause damage to important biological structures, such as proteins, carbohydrates, lipids, and nucleic acids, and may enhance the inflammatory response via NADPH oxidase [ 65 ] or myeloperoxidase action [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then chloramine-T (28 mM) was added to all samples and they were incubated for a period of 1 h at 37 °C. Sodium azide (1 mM) as a preservative was used in the experiments [9,86]. Subsequently, all samples were dialyzed and frozen until the time of measurement of glycoxidation products (AOPPs and AGEs).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we propose that AG attenuates the fibrogenic response in T2DM rats, considering that AG reduces AGEs, advanced oxidation protein products (AOPP) (68), and inhibits iNOS activity (69,70), thus reducing oxidative-associated cardiac fibrosis. This was observed in vivo by αSMA IHC, Sirius red/Fast green and Masson's trichrome staining, and confirmed by the in vitro experiments on myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have documented the underlying possible mechanism of AG in diabetes associated cardiac fibrosis, however, the effect of AG on collagen type I deposition through SMAD2/3-ERK1/2 via AGE/RAGE signaling represents the novelty of this study. These can be explained due to the glycation and AOPP-inhibiting properties of AG widely described in the scientific literature (68,71).…”
Section: Discussionmentioning
confidence: 99%